Management af a Patient with Guillain-Barré Syndrome Miller Fisher Type and Hospital-Acquired Pneumonia in the Intensive Care Unit : a Case Report - Suwarman; Natapraja, Tresna Kusumah (Journal of Society Medicine, 2024)
Introduction: Guillain-Barré Syndrome (GBS) is an acute, flaccid polyneuropathy that occurs following an infection and is mediated by an autoimmune process. Patients with GBS frequently experience respiratory complications that necessitate mechanical ventilation. Neurological impairments associated with GBS, such as decreased airway patency, ineffective cough, and difficulty swallowing, increase the risk of pulmonary infections like hospital-acquired pneumonia (HAP). Case Report: We present the case of a 59-year-old woman who experienced respiratory failure due to GBS and HAP and required treatment in the Intensive Care Unit (ICU). The patient was managed with Therapeutic Plasma Exchange (TPE), which resulted in clinical improvement. It took 18 days for the patient to be weaned off mechanical ventilation. Conclusion: A detailed review of the management strategies for GBS and HAP is essential to enhance future treatment approaches and ensure they align with current literature.